Some Thougts About Accounting Conceptual Framework and Standards For Awqaf Institutions - Muhammad Akhyar Adnan, Maliah Sulaiman, Putri NOr Sad Megat Mohd Nor (Trisakti University, 2007)
the awqaf institutions are, perhaps the less developed Islamic Financial Institutions compared to banking, insurance and zakat